Changes in Students' Cognitive Structure on the Concept of Diffraction and Light Interference Using PhET Virtual Simulation - Syifa, Almira; Darma Putra, Ngurah Made; Darsono, Teguh; Rohim, Ahmad Minanur (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
The concept of diffraction and interference of light is one of the abstract concepts of physics. The process of light diffraction and interference occurs in the abstract. Learning about diffraction and light interference requires media that represent the events. Cognitive structures can represent the quality of students' understanding. Learning Physics is easier to understand through direct experience in the form of practicum. Abstract Physics concepts will be easier to learn with the appropriate visualization. One of the virtual practicums' media uses PhET virtual simulations to improve students' cognitive structure is measured using concept map questions and supported by description questions. The purpose of this research is to increase the cognitive structure of students by using PhET. This research is quantitative research and the experimental design used the experiment method. There are three groups in the experiment, that is a virtual simulation, a real practicum as an experiment class, and a control class. The results of the one-way ANOVA test on the concept map questions showed a significance value (p) <0.05, meaning that there were differences in cognitive structure between groups. The significance value (p) between the virtual simulation group and the real practicum group was 0.014, while the significance value between the virtual simulation group and the control class was 0.00, meaning that there was a significant difference in learning effectiveness between groups. Based on the data of the research concluded that physics learning assisted by virtual simulations can develop students' cognitive structures on the concepts of diffraction and light interference.